2012
DOI: 10.1161/circulationaha.111.080275
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Chemokine Release Supports a Bimodal Mechanism of Spinal Cord Ischemia and Reperfusion Injury

Abstract: Background-Paraplegia remains a devastating complication of thoracic aortic surgery. The mechanism of the antecedent spinal cord ischemia and reperfusion injury (IR) remains poorly described. IR involves 2 injuries, an initial ischemic insult and subsequent inflammatory amplification of the injury. This mechanism is consistent with the clinical phenomenon of delayed onset paraplegia. This study sought to characterize the inflammatory response in the spinal cord after IR and hypothesized that this would support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
76
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 33 publications
9
76
0
1
Order By: Relevance
“…Compared with the SCIR-injured rats, the RESV and MP treatments substantially suppressed the concentrations of these pro-inflammatory cytokines, indicating their anti-inflammatory potential. Our results are supported by those of Smith et al, who evaluated inflammatory chemokine concentrations (interleukin-1β, IL-6 and TNF-α) and reported elevated levels of these inflammatory cytokines after SCIR [26]. Furthermore, RESV can effectively improve cerebral blood flow by crossing the blood-brain barrier and exhibits protective effects against ischemic injury by decreasing glial cell activation and thus positively alleviating oxidative stress and the inflammatory cascade.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with the SCIR-injured rats, the RESV and MP treatments substantially suppressed the concentrations of these pro-inflammatory cytokines, indicating their anti-inflammatory potential. Our results are supported by those of Smith et al, who evaluated inflammatory chemokine concentrations (interleukin-1β, IL-6 and TNF-α) and reported elevated levels of these inflammatory cytokines after SCIR [26]. Furthermore, RESV can effectively improve cerebral blood flow by crossing the blood-brain barrier and exhibits protective effects against ischemic injury by decreasing glial cell activation and thus positively alleviating oxidative stress and the inflammatory cascade.…”
Section: Discussionsupporting
confidence: 89%
“…The abovementioned biochemical analyses revealed that NAR attenuates the concentration of various inflammatory markers; to confirm these results, the protein expression of TNF-α and NF-κB p65 were quantified. Previous studies have revealed that the activation of NF-κB p65 is a crucial event during the induction of SCII in several animal models [3,27]. As indicated above, the protein expression of both TNF-α (cytosolic fraction) and NF-κB p65 (nuclear fraction) was significantly upregulated during SCII due to excessive oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…Few of the shortcomings include lack of an anatomically clear ischemic penumbra, which is the target of many neuroprotective drugs, and the absence of reperfusion. It is well known that reperfusion following ischemia is characterized by changes like increased production of reactive oxygen species, infiltration of inflammatory cells and increased cytokine production [30][31][32] . Lack of reperfusion in PT means the changes associated with reperfusion injury in SC will remain difficult to study using this model.…”
Section: Discussionmentioning
confidence: 99%